Gambaran Cakupan Imunisasi Dasar Lengkap (IDL) di Puskesmas Kadungora Garut Tahun 2024 - Nita Kardilah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Complete Basic Immunization (CBI) coverage is a crucial indicator in the effort to prevent vaccine-preventable diseases and reflects the performance of primary healthcare services. In 2024, Garut Regency recorded a CBI coverage rate of 78.29%, while Kadungora Public Health Center reported the lowest rate at 65.07%. This study aims to describe the CBI coverage at Kadungora Public Health Center during the year 2024. The research used a quantitative descriptive method with a secondary data analysis approach. The population and the sample consisted of 813 infants who received immunizations and were recorded at Kadungora PHC between January and December 2024. The results showed coverage for each type of immunization as follows: HB-0 (71,7%), BCG (90%), DPT-HB-Hib 1–3 (91%,92,3%,91,9%), OPV 1–4 (90.3%,91,5%,92,1%,91%), IPV 1–2 (81,4%,70,6%), MR (91,1), PCV I–II (81,1%,82,2%), and Rotavirus I–III (58.18%–69.13%). The lowest coverage was found in HB 0, Rotavirus and IPV immunizations. These findings highlight the need for targeted interventions to improve CBI coverage, particularly for vaccines with the lowest achievement rates, in order to meet the national immunization coverage targets more evenly.